Inconvenient, reaches and potentialities of the wireless networks in the Education and its integration with the R + D. - Roa, Pablo F. (2007)
The wireless networks have had a great impact in the foreign educational Campus being in Argentina a recent technology. They possess characteristics in equable with regard to the mobility and flexibility of the environment where they can be located. In our city is born the concrete need to link the Technological Center of the Seaboard, the Campus of the National University of the Litoral and the CERIDE (central regional of investigation and development) especially working parties in parallel computation of said institutions. Due to that these centers are found arranged geographically to distances that do not exceed the 1300 mts. the technology wireless permits to present a primary solution of links, being able to pass to a technology of in agreement fiber the demands of traffic be increased and the projects. This solution permits to carry out happiness plan without altering the nature Preserve of the Seaboard (Ecological Reserve) situated between the Campus and the Technological Center. In the present I work the benefits of this technology they are analyzed and their implementation.